Sanctity and Theatricality. Exploring the Conversion and Representations of Saint Thaïs through Hagiography, Literature, and Art post the Council of Trent - Massimo Leone (Ocula)
This study concentrates on the multifaceted representations of Saint Thaïs across hagiography, literature, and art, focusing on the narratives of her conversion post the Council of Trent. Exploring verbal and visual texts, the paper identifies four key perspectives: the historical veracity of Saint Thaïs, the evolution of her depictions through cultural and religious history, a semiotic analysis of genre transposition, and her relevance to faith and conversion themes. Furthermore, it allows a general reconsideration of the semiotic value of saints, highlighting how their portrayals reflect and influence the interrelation between religious belief and cultural narratives. This comprehensive examination sheds light on the intricate interplay between religious doctrine and cultural expression in shaping the legacy of Saint Thaïs.